A bifunctional asymmetric electrochromic supercapacitor with multicolor property based on nickel oxide/vanadium oxide/reduced graphene oxide - Mohanadas, Dharshini; Azman, Nur Hawa Nabilah; Sulaiman, Yusran (Elsevier, 2022)
A ternary nickel oxide/vanadium oxide/reduced graphene oxide (NiO/V2O5/rGO) was designed as a positive electrode of an asymmetric electrochromic supercapacitor. The uniform distribution of the elements (C, Ni, O, V) in the wrinkle-like sheet of NiO/V2O5/rGO was observed via elemental mapping. NiO/V2O5/rGO electrode demonstrated an outstanding specific capacitance of 1265.5 F/g compared to rGO (40.9 F/g), NiO (130.5 F/g), V2O5 (521.2 F/g) and NiO/V2O5 (707.3 F/g). The developed nickel oxide/vanadium oxide/ reduced graphene oxide//copper-based metal-organic framework/reduced graphene oxide (NiO/V2O5/rGO//MrGO) electrochromic supercapacitor (EC-SC) device that operated at wide operating potential successfully delivered maximum specific energy of 41.4 Wh/kg and excellent cycling stability (capacitance retention of 92.2%) over 4000 CV cycles. Interestingly, the level of energy stored in the prepared asymmetric EC-SC device can be visually detected as it implied color changes from dark green to orange. NiO/V2O5/rGO//MrGO with excellent optical and supercapacitive properties is designated as a promising electroactive material for next generation electrochromic supercapacitors.